Enhanced recognition of plasma proteins in a non-native state by complement C3b. A possible clearance mechanism for damaged proteins in blood - Ramadass, Mahalakshmi (Mol Immunol, 2014)
Complement C3 is a key fluid-phase protein of the immune system that covalently tags pathogenic cells and molecules for subsequent clearance. Previously, we reported that complement activation results in the formation of multiple C3b:plasma protein complexes in serum. However, it is not known if C3b attaches to any plasma protein in close proximity or preferentially binds damaged proteins. The objective of this study was to determine if C3b couples to plasma proteins in a non-native state and if this could be a potential mechanism to detect and clear damaged proteins from the blood. Using a purified in vitro system with alternative pathway proteins C3, factors B and D it was observed that guanidinium-HCl denaturation of three purified plasma proteins (albumin, alpha-1 proteinase inhibitor, vitamin D binding protein) greatly increased their capacity to form covalent complexes with C3b. However, native vitamin D binding protein, covalently attached to C3b, still retained the ability to bind its natural ligand G-actin, indicating that C3b links to plasma proteins in their native configuration but denaturation substantially increases this interaction. Serum complement activation generated a large number of C3b:plasma protein complexes that bound red blood cell membranes, suggesting a CR1-mediated clearance mechanism. Thermally denatured (60°C) serum activated the alternative pathway when added to fresh serum as evidenced by factor B cleavage and iC3b generation, but this heat-treated serum could not generate the pro-inflammatory peptide C5a. These results show that C3 recognizes and tags damaged plasma proteins for subsequent removal from the blood without triggering proinflammatory functions.